Staging France between the World Wars : performance, politics, and the transformation of the theatrical canon - McCready, Susan, 1970- (Lexington Books, 2016)
Staging France between the World Wars analyzes the rise of the modernist aesthetic in French stagecraft between the world wars. Focusing on interwar productions of the classics, it demonstrates that modernist directors had a significant and lasting impact on the academic canon of theater: they introduced a youthful, farcical Molière, reshuffled the hierarchy of Romantic playwrights, and introduced a generation to a more authentic Shakespeare.